Orientasi Pedagogik dan Perubahan Sosial Budaya terhadap Kemajuan Ilmu Pendidikan dan Teknologi - Firdaos, Rijal (Universitas Islam Negeri Raden Intan Lampung, 2015)
Advances in information technology and communication today has a lot to change the culture and civilization of the Indonesian nation with all its positive and negative impacts. As an entity related to the culture and civilization, education in various parts of the world experienced a fundamental change in the era of globalization. There are many advances in science and technology that could be enjoyed by mankind. But today, there are still some weaknesses of education in Indonesia, of which include; First, lack of access to education, secondly, improving governance. Third, improving the quality of educational institutions and out put. This research aims to determine the orientation of Pedagogic and sociocultural changes towards the advancement of science and technology education that includes the role of education in the era of globalization, the future school model, the development of gender-based education, And equivalent gender in education.